The prevalence of polycystic ovary syndrome in a community sample assessed under contrasting diagnostic criteria - W. A. March; Vivienne Moore; Kristyn Willson; David I. W. Phillips; Robert J. Norman; Michael J. Davies (2009)
Polycystic ovary syndrome (PCOS) is considered to be the most common endocrine disorder in women of reproductive age, yet debate over appropriate diagnostic criteria and design limitations with sampling methodology have left some doubt as to the actual prevalence in the community. The objective of this study was to create a representative prevalence estimate of PCOS in the community under the National Institutes of Health (NIH) criteria and the more recent Rotterdam consensus criteria and Androgen Excess Society (AES) criteria. A retrospective birth cohort study was carried out in which 728 women born during 1973–1975 in a single maternity hospital were traced and interviewed in adulthood (age = 27–34 year; n = 728). Symptoms of PCOS (hyperandrogenism, menstrual dysfunction and polycystic ovaries) were identified by examination and the presence of polycystic ovaries in those that did not consent to the ultrasound were imputed. The estimated prevalence of PCOS in this birth cohort using the NIH criteria was 8.7 ± 2.0% (with no need for imputation). Under the Rotterdam criteria, the prevalence was 11.9 ± 2.4% which increased to 17.8 ± 2.8% when imputed data were included. Under the AES recommendations, PCOS prevalence was 10.2 ± 2.2%, and 12.0 ± 2.4% with the imputed data. Of the women with PCOS, 68–69% did not have a pre-existing diagnosis. The Rotterdam and AES prevalence estimates were up to twice that obtained with the NIH criteria in this, as well other prevalence studies. In addition, this study also draws attention to the issue of many women with PCOS in the community remaining undiagnosed.